Lightweight Concrete With Mixed Foam Agent, Polymer and Bonding to Reach 300 Kg/Cm² - Siti Rukmayani Japar; Freedy Kurniawan (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2020)
Lightweight concrete is very much developed because of its benefits that can reduce the weight of the building itself, so that the earthquake effect on buildings can be minimized. By using Foam Agent Technology, it will add air pores which can reduce the specific gravity of normal concrete. To achieve the K 300 Concrete Quality with Light Weight, the researchers added Polymer and Polymer and Bonding mixture to the Concrete mixture using Foam Agent technology. From the research conducted by researchers, it was found that Foam Agent is able to help concrete become lighter by 13%. This research was also able to obtain the optimum compressive strength results with a light weight, the Light Concrete study with the addition of Foam Agent, Polymer and Bonding with a quality of 267 kg / cm² or equivalent to Fc 22 with a weight of 1877 Kg / cm³ and an efficiency coefficient of 14% which is higher than normal Concrete K 300 with a magnitude of 13%.